Keeping taonga warm : Aotearoa New Zealand's museums and Maori tapu material : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Anthropology, Palmerston North, Social Anthropology Programme, School of Global Studies, Massey University - Park, Marilyn (Massey University, 2003)
This thesis is an interpretative viewpoint from a Aotearoa New Zealand tauiwi, of the importance of the spiritual meaning of taonga and their related concepts of tapu, mana and wairua to Maori, both in the past and today. It is concerned primarily with how taonga and their tapu nature have been addressed by Aotearoa New Zealand's museums, historically and contemporarily, and by the anthropologists and archaeologists and ethnologists working within them. While related issues include all indigenous secret and sacred material, both tangible and intangible, I am primarily interested in how museum professionals, expecially anthropologists and archaeologists working within New Zealand Museums, have incorporated the concept of tapu into their engagement with Maori taonga, and how they resolve their own beliefs with those of Maori. I am specifically concerned with how Maori taonga are kept spiritually ' warm,' by non-Maori museum personnel concerned with their physical care. This involves an analysis of museum traditions and past historical influences now affecting Aotearoa New Zealand today. This discussion begins with an explanation of the author's ontological viewpoint and reasons for writing this, and sets the terms of reference for the following discussions. Chapter One examines of the meaning of tapu, taonga and their related concepts, the way in which early writers and ethnologists have dealt with this subject historically, and the impact that this had on the current museological climate as well as interpretations by current writers including Maori and anthropologists. Chapter Two shows how scientific interests took precedence over Maori tapu concerns in early museum practice, both in collecting habits, display and in the interpretation of Maori tikanga, by ethnologists and museum management. Chapter Three discusses the recent changes in the management of some Aotearoa New Zealand's museums, the effect of professional guidelines and specific pieces of legislation on both Maori and museums, nationally and internationally. Recent changes include bicultural management within some museum management structures, iwi liaison committees within others, and current Maori initiatives in respect to the management of koiwi tangata. Chapter Four examines the impact that the changing attitudes towards Maori issues by non-Maori staff have had in Aotearoa New Zealand's Museums, regarding Maori access to taonga, the handling of taonga by non-museum staff, conservation issues and what the situation is today and where it is going. In the Conclusion I argue that, rather than a growth in understanding of Maori concerns regarding the care of and access to taonga held in Aotearoa New Zealand's museums, and of their tapu regulations, and the implications of these to the current well-being of specific iwi, a process of 'managerialization' of tapu concerns has been instigated in all major museums in Aotearoa New Zealand, and with some variations, within some other smaller ones. This has resulted in the decision making passing into the hands of iwi or joint management committees, whereby individual curators, collection managers and ethnologists no longer need to understand these issues deeply. Finally, I emphasise that only museums who actively pursue a co-operative relationship with their local iwi or marae will be visited by the local Maori community and continue to be allowed to continue to care for these important links from the past with the Maori of today. This should involve a repatriation of stolen taonga, koiwi tangata and mokomokai and retraining of museum staff in tikanga and Maori issues. It is not enough to 'pass the buck' and ignore the issues involved.
Keywords: Maori New Zealand people; Museums; Antiquities; Collection Preservation; Material culture; Cultural property; Taonga; Tāngata whenua; Mana whakairo hinengaro; Museums and minorities; Tapu; Whare taonga; Mana whakahaere